Peranan Manajemen Pedidikan Pondok Pesantren Dalam Menumbuhkan Budaya Disiplin Santri (Studi di pondok Pesantren Al-Wasilah Sigenjah Waringinkurung) - Hikmah faujiah; Anis Zohriah; Anis Fauzi (Journal on Education, 2024)
This study explores the role of education management in Al-Wasilah Sigenjah Waringinkurung Islamic Boarding School in fostering student discipline. The management of Islamic boarding school education plays an important role in shaping the attitude and behavior of student discipline by implementing policies, learning programs, and structured daily activities. This study uses a qualitative approach with a case study method, which involves direct observation, in-depth interviews with Islamic boarding school caregivers, teaching staff, and students, as well as analysis of related documents. The study results show that student discipline can be formed through effective management, where factors such as pesantren leaders, continuous supervision, and the provision of appropriate sanctions and rewards contribute significantly to the successful implementation of discipline. This study provides important insights for the development of a more optimal education management system in Islamic boarding schools to support the formation of disciplined and responsible student character.